2022
DOI: 10.1039/d1cp05760j
|View full text |Cite
|
Sign up to set email alerts
|

Zooming in on the initial steps of catalytic NO reduction using metal clusters

Abstract: The study of reactions relevant to heterogeneous catalysis on the surface of well-defined metal clusters with full control over the number of consituent atoms and elemental composition can lead to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 120 publications
(222 reference statements)
0
26
0
Order By: Relevance
“…We find that, first, NO tends to adsorb on the niobium clusters via the N–Nb bonding, and the N–O bond can be spontaneously dissociated for all four studied systems within the 0.1–10 ps time scale, which means collisional stabilization of helium can be ignored (For more details on other clusters, see Figure S29, ESI.). This is accessible with a low energy barrier of the transition states (TS) which result from the formation of N/O binding onto the Nb atoms. , The reactivity of the single atomic cation Nb + follows the free radical mechanism just like the other transition metal ions such as Sc, Ti, and V, , whereas the dissociatively adsorbed Nb n NO + clusters will allow for Nb–Nb bond cleavage (to form Nb n –1 N + or Nb n –1 O + ) along with NbO/NbN loss. For the relatively larger cluster Nb 10 + , the N atom forms hollow site binding with an energy gain of 2.99 eV which allows for the subsequent dissociation reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that, first, NO tends to adsorb on the niobium clusters via the N–Nb bonding, and the N–O bond can be spontaneously dissociated for all four studied systems within the 0.1–10 ps time scale, which means collisional stabilization of helium can be ignored (For more details on other clusters, see Figure S29, ESI.). This is accessible with a low energy barrier of the transition states (TS) which result from the formation of N/O binding onto the Nb atoms. , The reactivity of the single atomic cation Nb + follows the free radical mechanism just like the other transition metal ions such as Sc, Ti, and V, , whereas the dissociatively adsorbed Nb n NO + clusters will allow for Nb–Nb bond cleavage (to form Nb n –1 N + or Nb n –1 O + ) along with NbO/NbN loss. For the relatively larger cluster Nb 10 + , the N atom forms hollow site binding with an energy gain of 2.99 eV which allows for the subsequent dissociation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This is accessible with a low energy barrier of the transition states (TS) which result from the formation of N/O binding onto the Nb atoms. 56,57 The reactivity of the single atomic cation Nb + follows the free radical mechanism just like the other transition metal ions such as Sc, Ti, and V, 28,58−60 whereas the dissociatively adsorbed Nb n NO + clusters will allow for Nb−Nb bond cleavage (to form Nb n−1 N + or Nb n−1 O + ) along with NbO/NbN loss. For the relatively larger cluster Nb 10 + , the N atom forms hollow site binding with an energy gain of 2.99 eV which allows for the subsequent dissociation reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mackenzie and coworkers used mass spectrometry to investigate the adsorption of NO molecules onto Rh cluster cations, observing NO reduction for several cluster sizes under low-pressure conditions. They also investigated the geometrical structures of Rh clusters with IR multiple photon dissociation (IRMPD) spectroscopy. , Ichihashi and coworkers studied NO adsorption onto alloyed Rh clusters, finding NO reduction for alloys with Al and V . Recently, we conducted a series of spectroscopic experiments investigating the adsorption of NO onto clusters of several elements at sufficiently higher pressures, allowing thermal equilibration of the adsorption product. In the spectroscopic study of NO adsorption on cationic Rh clusters, Rh n + ( n = 6–16), we found that for all n studied, NO predominantly adsorbs in the molecular form on on-top sites of Rh n + , and that only a small fraction adsorbs dissociatively . For dissociative adsorption, the O atom tends to bind to a bridge site, whereas the N atom is found on either a bridge or a hollow site.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NO itself can react in different ways as it can dissociate (over Rh, Pt and Pd), dimerize (over Cu) upon adsorption or it can simply exhibit molecular adsorption [16] . For effective removal of NO via a DeNOx process, it is the dissociation of NO that is desired, whereby it should be noted that the behavior of the NO adsorbate and the clusters are obviously mutually related [17] …”
Section: Introductionmentioning
confidence: 99%
“…[16] For effective removal of NO via a DeNOx process, it is the dissociation of NO that is desired, whereby it should be noted that the behavior of the NO adsorbate and the clusters are obviously mutually related. [17] As numerous temperature-dependent desorption studies have shown that the precise stoichiometry and reaction pathway may depend on the specific local environment of the transition metal, the study of model systems (such as nanoclusters) in a realistic environment are of major importance. [18] The behavior of such nanosized metal clusters on oxide structures has been studied extensively using X-ray absorption spectroscopy (XAS) and Anomalous Wide Angle X-ray Scattering (AWAXS) as they offer information of the atomic arrangement at nanometer scale.…”
Section: Introductionmentioning
confidence: 99%